APPLE PULP ENZYME TREATMENT WITH ULTRAZYM®AFP-L AND PANZYM®YIELDMASH - ZIELINSKI, ACÁCIO ANTONIO FERREIRA; PRESTES, ROSILENE APARECIDA; BARBOSA, RHUANE; NOGUEIRA, ALESSANDRO; WOSIACKI, GILVAN (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2014)
The present study aimed to verify the influence of the enzymatic preparations Ultrazym®AFP-L and Panzym®YieldMASH over the yield and chemical quality of apple juice. The process was optimised according to two parameters: temperature and enzyme concentration in a one hour-long run. The results of physical and chemical analysis were further submitted to multivariate statistical procedure aimed at pattern recognition. The exploratory and classificatory modeling discriminated the samples with 100 % correlation. The results of the experimental factorial design pointed to enzyme concentration as being the main factor that increased the yield. The concomitant observation of data using Principal Component Analisys (PCA) exploratory tools showed the tendency to separate the control samples according to higher content of phenolic compounds, glucose, pH and colour; the Ultrazym® AFP-L samples according to total acidity; and the Panzym®YieldMASH samples according to higher sugar content. It was concluded that the utilization of industrial enzymes in apple processing increases the yield of juice and decreases the amount of pomace.